Revised Morning Loops of the Arabidopsis Circadian Clock Based on Analyses of Direct Regulatory Interactions. - Sally Adams; Ian Manfield; Peter Stockley; Isabelle A Carré (PLoS ONE, 2015)
The network structure of the plant circadian clock is complex and direct regulatory interactions between individual components have proven particularly difficult to predict from genetic analyses. Here, we systematically investigate in vivo binding interactions between the morning-specific transcription factor, LATE ELONGATED HYPOCOTYL (LHY) and the promoters of other components of the network. We then demonstrate the functionality of these interactions by testing the responsiveness of the target gene to an ethanol-induced change in expression level of the LHY protein. We uncover novel, negative autoregulatory feedback loops from LHY and the closely related CIRCADIAN CLOCK ASSOCIATED-1 (CCA1) onto their own and each other's expression. Furthermore we show that LHY acts as a repressor of all other clock components, including PSEUDO-RESPONSE REGULATORs (PRRs) 9 and 7, which were previously thought to be positive regulatory targets. These experimental results lead to a substantial revision of the morning loops of the clock.